(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2025)
The excitation cross-sections of the 4F and 5F states of atomic hydrogen by electron impact have been calculated at incident energies 1.00 to 42.25 Ry, using the hybrid theory, which is variationally correct. The present calculation is a single-channel or a distorted wave calculation. Partial waves ranged from \(L=3\) to 14 to obtain converged results. Excitations of higher states are needed for diagnostics of the solar and astrophysical plasmas. They are also needed to model plasma in fusion research, because they indicate the possibility that a state will be excited to a higher state when colliding with another state. Transition rates to the lower states can be measured by observing decays of the excited states.